Learning Strategies at SMA Muhammadiyah 3 Tulangan During Pandemic Covid-19 - Maulidya Putri Pratama; Muhlasin Amrullah (International Consortium of Education and Culture Research Studies, 2021)
This study aims to determine the strategies applied at SMA Muhammadiyah 3 Tulangan reinforcement in learning in the midst of the covid 19 pandemic. This scientific paper examines various aspects, including history, strategies, challenges, and effectiveness in learning. This research is a descriptive qualitative research. The data collections technique of this research is throught interview, documentation, and observation. Based on the results of the study include that SMA Muhammadiyah 3 Tulangan learning reinforcement takes place online and offline. The results of the study include that SMA Muhammadiyah 3 Tulangan reinforcement already hat its own building, the strategies used are online and offline, the challenges faced are the lack of maximum learning through online, and effectiveness in learning that is indirectly upgrading teachers’ understanding in using it. However, the offline or face to face learning strategy that is held lasts only for a short time. Therefore, the impact arising from the increase in education makes the learning system less condusive and makes students less understanding the material correctly.